Henrik Skovgaard Nielsen, Flemming Schmidt, Nils Arne Sørensen, Niels Kayser Nielsen, Verdens Historie 3. Fra 1945 til 1990, København: Gjellerup & Gad, 1990, 272 s., kr. 188,00. - Larsen, Arne (Politica, 1991)
-